2013
DOI: 10.1371/journal.pone.0073010
|View full text |Cite
|
Sign up to set email alerts
|

Patient Assessment of Chronic Illness Care, Glycemic Control and the Utilization of Community Health Care among the Patients with Type 2 Diabetes in Shanghai, China

Abstract: ObjectivesTo evaluate the relationship between Patient Assessment of Chronic Illness Care in community health centers and self-management behaviors and glycemic control and to examine the relationship between Patient Assessment of Chronic Illness Care in community health centers and the utilization of community health centers for monitoring and treating diabetes among the patients with type 2 diabetes.MethodsA questionnaire including self-management behaviors, glycemic control, Patient Assessment of Chronic Il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The mean score in Germany was highest for the subscale 'Delivery system design/decision support' and contrary to our findings, the lowest for 'Goal setting/tailoring' [ 28 ]. PACIC score in China was associated with the utilization of community health centers, where patients’ trusting in community health centers depended on the quality of chronic care [ 32 ]. Our study results were similar to Petersen et al [ 28 ] and Ludt et al revealing that higher PACIC scores were associated with more frequent FD contacts [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean score in Germany was highest for the subscale 'Delivery system design/decision support' and contrary to our findings, the lowest for 'Goal setting/tailoring' [ 28 ]. PACIC score in China was associated with the utilization of community health centers, where patients’ trusting in community health centers depended on the quality of chronic care [ 32 ]. Our study results were similar to Petersen et al [ 28 ] and Ludt et al revealing that higher PACIC scores were associated with more frequent FD contacts [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other markers of person-centered care in diabetes management include health-related quality of life [ 10 ], diabetes distress [ 11 ], and perception of chronic illness care [ 12 ]. Health-related quality of life reflects the combined impact of an individual’s physical, psychological, and social well-being on health-related quality of life, and in patients living with diabetes, lower quality of life is associated with poorer clinical outcomes such as glycemic control [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the PACIC was correlated with other quality of care measures, including care experience surveys and the receipt of laboratory tests and self‐management support . However, its association with health outcomes such as glycaemic control and blood cholesterol levels remains equivocal …”
Section: Introductionmentioning
confidence: 99%
“…4,[6][7][8][9][10] However, its association with health outcomes such as glycaemic control and blood cholesterol levels remains equivocal. 11,12 While quality assessments from patient perspectives reflect the technical quality of providers (e.g. providers' adherence to recommended care), it may also be influenced by the customer quality (attributes of patients that enable them to participate more effectively in the health-care delivery system).…”
Section: Introductionmentioning
confidence: 99%